IMPROVING STUDENTS’ SPEAKING ABILITY BY USING RECIPROCAL TEACHING STRATEGY AT THE TWELVE GRADE STUDENTS OF SMKN 1 RAMBAH ROKAN HULU REGENCY - Ahmad, Zulpahmi (Edu Research, 2014)
The purpose of this research was to know the extent of reciprocal teaching can improve speaking skill of student of the third grade level of SMKN 1 Rambah Kab. Rokan Hulu and to know the factors influence the improvement of speaking skill of student of the third grade of SMKN 1 Rambah by using Reciprocal Teaching. This research is an action research that is done by three cycles. One cyrcle consist of fivemeetings. The participants of the study are 39 students. The data were collected by speaking test, observation checklist, filed notes/video recording, and interview. The finding showed that the significant influences of Reciprocal Teaching Strategy in teaching speaking